Auditory object salience: human cortical processing of non-biological action sounds and their acoustic signal attributes - Lewis, James W.; Talkington, William J.; Tallaksen, Katharine C.; Frum, Chris A. (Frontiers in Systems Neuroscience, 2012)
Whether viewed or heard, an object in action can be segmented from a background scene based on a number of different sensory cues. In the visual system, salient low-level attributes of an image are processed along parallel hierarchies, and involve intermediate stages, such as the lateral occipital cortices, wherein gross-level object form features are extracted prior to stages that show object specificity (e.g. for faces, buildings, or tools). In the auditory system, though relying on a rather different set of low-level signal attributes, a distinct acoustic event or “auditory object” can also be readily extracted from a background acoustic scene. However, it remains unclear whether cortical processing strategies used by the auditory system similarly extract gross-level aspects of “acoustic object form” that may be inherent to many real-world sounds. Examining mechanical and environmental action sounds, representing two distinct categories of non-biological and non-vocalization sounds, we had participants assess the degree to which each sound was perceived as a distinct object versus an acoustic scene. Using two functional magnetic resonance imaging (fMRI) task paradigms, we revealed bilateral foci along the superior temporal gyri (STG) showing sensitivity to the “object-ness” ratings of action sounds, independent of the category of sound and independent of task demands. Moreover, for both categories of sounds these regions also showed parametric sensitivity to spectral structure variations—a measure of change in entropy in the acoustic signals over time (acoustic form)—while only the environmental sounds showed parametric sensitivity to mean entropy measures. Thus, similar to the visual system, the auditory system appears to include intermediate feature extraction stages that are sensitive to the acoustic form of action sounds, and may serve as a stage that begins to dissociate different categories of real-world auditory objects.